New Role for L-Arginine in Regulation of Inducible Nitric-Oxide-Synthase-Derived Superoxide Anion Production in Raw 264.7 Macrophages. (18th December 2011) - Pekarova, Michaela; Lojek, Antonin; Martiskova, Hana; Vasicek, Ondrej; Bino, Lucia; Klinke, A.; Lau, D.; Kuchta, Radek; Kadlec, Jaroslav; Vrba, Radimir; Kubala, Lukas
Abstract : Dietary supplementation with L-arginine was shown to improve immune responses in various inflammatory models. However, the molecular mechanisms underlying L-arginine effects on immune cells remain unrecognized. Herein, we tested the hypothesis that a limitation of L-arginine could lead to the uncoupled state of murine macrophage inducible nitric oxide synthase and, therefore, increase inducible nitric-oxide-synthase-derived superoxide anion formation. Importantly, we demonstrated that L-arginine dose- and time dependently potentiated superoxide anion production in bacterial endotoxin-stimulated macrophages, although it did not influence NADPH oxidase expression and activity. Detailed analysis of macrophage activation showed the time dependence between LPS-induced iNOS expression and increased O 2 ∙ - formation. Moreover, downregulation of macrophage iNOS expression, as well as the inhibition of iNOS activity by NOS inhibitors, unveiled an important role of this enzyme in controlling O 2 ∙ - and peroxynitrite formation during macrophage stimulation. In conclusion, our data demonstrated that simultaneous induction of NADPH oxidase, together with the iNOS enzyme, can result in the uncoupled state of iNOS resulting in the production of functionally important levels of O 2 ∙ - soon after macrophage activation with LPS. Moreover, we demonstrated, for the first time that increased concentrations of L-arginine further potentiate iNOS-dependent O 2 ∙ - formation in inflammatory macrophages.